Aluminium Phosphide Poisoning which Occuring with an Unusual Accident and Resulting in Death: Case Report - Karadeniz, Hülya; Boz, Halil; Ketenci, Hüseyin Çetin (The Bulletin of Legal Medicine, 2018)
Aluminium phosphide is an insecticide that shows highly toxic activity when it reacts with water or moister and becomes phosphine. Because it has high diffusion capacity, it can kill all the organisms in different growth phases in the area that it is used. However, it is used frequently due to not to find rests on plants. There is not a specific antidote for aluminium phosphide and mortality from 30% to 100% in poisoning and it is related with exposure. In this study, we present 13 years girl case who was poisoned by aluminium phosphide. He was found in his apartment which is at first floor, after fumigation of food store at the basement. We aim to evaluate by autopsy findings, chemical and histopathological findings together and to discuss with literature results. In addition, we want to discuss about solution of uncontrolled dealing and using of aluminium phosphide in our country.
Keywords: Aluminum phosphide; poisoning; autopsy; toxicology